Intrinsic Motivation Preference on Volunteer In Indonesia International Work Camp - Ramadhan, Muhammad Bira; Darmastuti, Darmastuti (Faculty of Economics and Business Diponegoro University, 2015)
Intrinsic motivation has several factors (instrument) contained on it.There are 4 factors on intrinsic motivation which is owned by the volunteers were examined in this study, the factors are advancement, recognition, achievement and responsibility. Sample in this study were volunteers who carry out voluntary activities in Indonesia International Work Camp (IIWC) were totaled 72. Rank Spearman Correlation Test, Non-Parametric Mann Whitney Test, and Kruskall Wallis Testare used in this research. The results showed that the preference factors intrinsic motivation of volunteers in the organization Indonesia International Work Camp from the first to the fourth rank is: Factor Responsibility, Achievement Factor, Advancement and Recognition Factor. There is a negative correlation from the four factors of intrinsic motivation are not significantly different between the working period. There are differences in preferences between the serving time of less than 3 years and more than 3 years on the choice of intrinsic motivation factors. Volunteer with serving time of less than 3 years is selecting factors of achievement as a major factor possessed intrinsic motivation on his involvement with organized and from volunteer work period of more than 3years of selecting the responsibility of achievement as a major factor intrinsic motivation owned on his involvement in the organization. Based on the level of participation, it is showed that there is a significant difference in the factor of self-development potential, achievement, and responsibility. Volunteer with the level of active, participation prefers advancement as a potential factor intrinsic motivation factors as the most motivating, while the participation rate which is less active prefer achievement factors intrinsic motivation factors are the most motivating, and at the level of active participation prefers less responsibility factor motivating factor most intrinsically motivating.